Pengaruh Stress Kerja, Kepuasan Kerja dan Lingkungan Kerja Terhadap Organizational Citizenship Behavior (OCB): Studi Kasus pada PT IEI - Tri Mulyani Kartini; Etty Zuliawaty Zed (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of job stress, job satisfaction, and work environment on Organizational Citizenship Behavior (OCB) at PT IEI. The type of research applied is explanatory research, with a quantitative approach. The research population consists of 70 employees who work in the E2 production department of PT IEI. The sampling technique used is non-probability sampling with saturated sampling method. Data was collected through distributing questionnaires. Data analysis was performed using SmartPLS (Partial Least Square) version 3.2.9. The results of the analysis show that the effect of job stress on OCB has an original sample value of 0.132, with a T-Statistics value of 2.203 and P-Values of 0.028, which shows results greater than α (0.028 < 0.05). The effect of job satisfaction on OCB resulted in an original sample value of 0.221, T-Statistics 2.101, and P-Values 0.036, which is also greater than α (0.036 < 0.05). Meanwhile, the effect of work environment on OCB shows the original sample value of 0.572, T-Statistics 6.268, and P-Values 0.000, which is smaller than α (0.000 < 0.05). From the results of hypothesis testing conducted through path coefficient analysis, it can be concluded that: 1) job stress has a significant positive effect on OCB at PT IEI; 2) job satisfaction has a significant positive effect on OCB at PT IEI; 3) work environment has a significant positive effect on OCB at PT IEI.